Helping language development in early ages children through home school relations - Sudarmi Mauboi; Pinky Mulyaningtyas (Universitas Muhammadiyah Surabaya, 2020)
Abstract : This article aims to see and know the development of language in early childhood where in this case the author can find out what is the factor and what action is done to help the child in developing The development of language through school-home relations so that in schools and parents' homes, the neighborhood and educators in school can help the development of children's language so that what children get in their environment becomes a science that Useful for the growth and development of the data collection techniques used in this research is the technique of data collection and observation studies and qualitative research methods. Based on the technique of data collection and analysis, it can be concluded that the environment or school children will be able to be a factor that can be inhibited and can develop the language of early childhood so that the thing that is done is To help develop early childhood at home and school.Keywords: development, early childhood, languag